PENGARUH KEPEMIMPINAN TRANSFORMATIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Edward, Edward; Sumarni, Sumarni; Almaududi, Syahram (Jurnal Dinamika Manajemen, 2019)
The research purpose is to examine the effect of transformational leadership and motivation toward employee performance. Sample was chosen randomly as many as 124 employees. Data processing used Structural Equation Modeling (SEM) approach. The Result shows that transformational leadership and motivation have positive significance effect on empoyee performance. The dimension of transformational leadership which getting more attention is pushing employee to keep focus on organizational vision and mission. Motivation needs support too from leader to make employe to make employee feel satisfied and have good performance. Hence, it is recommended for further research train the leader to design the transformational leadership and employe motivtion increasing. Key Words: Transformational Leadership, Motivation, Employe Performance